Industrial Design, Competition and Globalization - Rusten, G.; Rusten, G.; Bryson, J.; Bryson, J. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
Economic activities are becoming increasingly globalised. One result being that for companies in developed market economies price-based competition is being replaced or supplemented by other forms of competitiveness. This book explores the shift towards design-based competitiveness and the escalation in the design-intensity of goods and services.